New multicollinearity indicators in linear regression models - Curto, J. D.; Pinto, J. C. (International Statistical Review, 2007)
Correlation is an important statistical issue for the Ordinary Least Squares estimates and for data-reduction techniques, such as the Factor and the Principal Components analyses. In this paper we propose new indicators for the multicollinearity problem in the multiple linear regression model.